2020
DOI: 10.1097/md.0000000000020436
|View full text |Cite
|
Sign up to set email alerts
|

Direct acting antiviral HCV treatment does not influence renal function

Abstract: HCV infection is associated with chronic kidney disease due to several mechanisms. Patients treated with interferon-based regimens demonstrate improved renal function and reduced incidence of chronic kidney disease. There is scarce evidence on the effect of direct acting antiviral regimens (DAAs) on renal function. We evaluated serial measures of renal function in a cohort of HCV-infected participants following completion of DAA-based treatment regimens. Measures of glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Historically, HCV has been difficult to treat in elderly patients due to its association with rapid progressive fibrosis and cirrhosis, along with a higher incidence of liver cancer compared to younger patients [10,11]. Additionally, there is an increased exposure risk of drug interactions between multiple concomitant medications for different common comorbidities in the elderly [12].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, HCV has been difficult to treat in elderly patients due to its association with rapid progressive fibrosis and cirrhosis, along with a higher incidence of liver cancer compared to younger patients [10,11]. Additionally, there is an increased exposure risk of drug interactions between multiple concomitant medications for different common comorbidities in the elderly [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that these therapies are effective and safe in patients with chronic hepatitis C infection who have end‐stage renal disease or have received a kidney transplant 26 . In addition, another analysis demonstrated that renal function was not impacted by DAAs in HCV‐infected patients 27 . In our analysis, we did not have data regarding longer‐term renal function, however, the postoperative dialysis rates were similar between HCV+ and HCV‐ cohorts.…”
Section: Commentmentioning
confidence: 60%
“…26 In addition, another analysis demonstrated that renal function was not impacted by DAAs in HCV-infected patients. 27 In our analysis, we did not have data regarding longer-term renal function, however, the postoperative dialysis rates were similar between HCV+ and HCV-cohorts. An important point is that not all patients likely seroconverted or received these therapies as most centers reserve DAA therapy for heart transplant recipients who seroconvert following HCV+ donor implantation.…”
Section: Commentmentioning
confidence: 91%
“…Recent study demonstrated that sofosbuvir-based therapy had transient eGFR decline during therapy with improvement off treatment. 32 The other studies showed no clinically relevant change in renal function among the majority of CHC patients received both sofosbuvir-based or sofosbuvir-free regimens, even until 24 months of post-treatment 33 or among patients with existing CKD, 34 and is safe and effective for ESRD HCV patients under maintenance hemodialysis. 35 However, long-term effects of direct acting antiviral on renal outcome remains unclear.…”
Section: Discussionmentioning
confidence: 97%